Lawas District Council (Majlis Daerah Lawas)/ Siti Fatimah Morsidi - Morsidi, Siti Fatimah (Universiti Teknologi MARA, Sarawak, 2013)
This chapter will discuss the background of the organization, objectives, and company policy or organization policy, mission and vision of the organization, organization structure, core business of the organization and other relevant information pertaining to the organization. I have chosen Lawas District Council as my practical training place.